C- C-ARM IMAGE-GUIDED HEAVY-ION THERAPY APPARATUS - MIN CHUL HEE; KIM JUNG IN; CHOI HYUN JOON; CHEON BO WI; YOU SEI HWAN (2023)
A C-arm image-guided heavy particle treatment apparatus, according to one embodiment of the present invention, comprises: a table supporting a subject; a C-arm frame disposed on one side of the table to be rotated in a first direction; an X-ray emission unit connected to one end of the C-arm frame and emitting X-rays to the subject; a heavy particle ray emission unit which emits heavy particle rays to the subject; a detection unit which is connected to the other end of the C-arm frame and detects X-rays having passed through the subject among the X-rays emitted to the subject or gamma rays emitted from the subject by the heavy particle rays emitted to the subject; and a collimator located at the top of the detection unit. According to the present invention, the C-arm image-guided brachytherapy apparatus can evaluate the condition of a patient by taking a tomography image with a low exposure dose. 본 발명의 일 실시예에 따른 C-암 영상유도 중입자 치료장치는, 대상체를 지지하는 테이블, 상기 테이블 일측에서 제1 방향으로 회전가능하게 배치되는 C-암 프레임, 상기 C-암 프레임의 일단에 연결되어 엑스선을 대상체에 조사하는 엑스선조사부, 중입자선을 상기 대상체에 조사하는 중입자선조사부, 상기 C-암 프레임의 타단에 연결되어 상기 대상체에 조사된 엑스선 중에서 상기 대상체를 투과하는 엑스선을 검출하거나 상기 대상체에 조사된 중입자선에 의해 상기 대상체에서 방출된 감마선을 검출하는 검출부 및 상기 검출부 상부에 위치하는 콜리메이터를 포함할 수 있다.